Kerja Sama Pemerintah dan Swasta Dalam Pengadaan Ruang Terbuka Hijau di Kabupaten Luwu Timur - Muh. Nur Adnan (Departemen Ilmu Pemerintahan Fisip Unhas, 2025)
The increasing population has led to a growing demand for public open spaces. To address this issue, land identification must be conducted effectively to maximize land allocation for public open spaces. Strategies for fulfilling the need for public open spaces should be aligned with regional environmental development, one of which is through the development of green open spaces. To optimize the development of green open spaces, the government collaborates with the private sector in managing and utilizing existing potentials. This study aims to provide an overview of the collaboration between the local government and the private sector in the provision of green open spaces in East Luwu Regency. This research employed a descriptive research design using a survey method. Data were collected through observation, interviews, and literature review. Information was gathered from various sources to ensure data adequacy. The data were then analyzed qualitatively through data organization, categorization, pattern identification, data selection, interpretation, description in the form of words and sentences, and conclusion drawing. The findings indicate that the collaboration between the local government and the private sector has been implemented based on the principles of public-private partnership. However, several aspects still require improvement, particularly the management and inventory of green open spaces in East Luwu Regency, which have not yet been carried out optimally. In addition, private sector participation remains relatively limited. Despite these challenges, the East Luwu Regency Government has made considerable efforts to improve environmental quality through the provision and development of green open spaces in collaboration with the private sector.